Simplified panicle fertilization is applicable to japonica cultivars, but splits are preferred in indica rice for a higher paddy yield under wheat straw return - Shu, Xiaowei; Zhang, Xiaoxiang; Wang, Shushen; Fu, Tong; Ding, Zhouyu; Yang, Ying; Wang, Zihan; Zhao, Shiru; Xu, Jiejiao; Zhou, Juan; Ju, Jing; Huang, Jianye; et al. (Frontiers in Plant Science, 2024)
The panicle fertilization strategy for japonica and indica rice under wheat straw return (SR) has not been updated, especially on elaboration of their impacts on spikelet differentiation and degeneration. This study aimed to verify the hypothesis that SR increases spikelets number by reducing the spikelet degeneration, and to explore the possibility of simplifying panicle fertilization. In three consecutive years, four varieties of japonica and indica rice were field grown in Yangzhou of Jiangsu Province, China. Six panicle fertilization rates and splits treatments were applied to SR and no straw return (NR) conditions. The results showed that SR promoted rice yield significantly by 3.77%, and the highest yields were obtained under the T2 [split panicle fertilization at the panicle initiation (PI) and spikelet primordium differentiation (SPD) stages] and T1 (panicle fertilization only at the PI stage) treatments, for indica and japonica rice respectively. Correlation and path analysis revealed that the number of spikelets per panicle was the most attributable to yield variation. SR significantly increased the concentration of alkali hydrolysable N in the soil 40 days after rice transplantation, significantly increased the nitrogen accumulation per stem (NA) during the SPD-pollen mother cell meiosis (PMC) stage, and increased the brassinosteroids level in the young panicles at the PMC stage, SR also reduced the degeneration rate of spikelets (DRS) and increased the number of surviving spikelets (NSS). The dry matter accumulation per stem was more important to increasing the NA in japonica rice at the PMC stage, whereas NA was more affected by the N content than the dry matter accumulation in indica rice. In japonica rice, panicle N application once only at the PI stage combined with the N released from SR was enough to improve the plant N content, reduce the DRS and increase the NSS. For indica rice, split application of N panicle fertilized at both the PI and SPD stages was still necessary to achieve a maximum NSS. In conclusion, under wheat SR practice, panicle fertilization could be simplified to once in japonica rice with a significant yield increase, whereas equal splits might be still optimal for indica rice.